THROMBOEMBOLIC COMPLICATIONS IN PATIENTS WITH ACUTE CALCULOUS CHOLECYSTITIS - Mariya Kavka (Acta Medica Leopoliensia)
The aim is the analysis of clinical and anamnestic, biochemical and hemostasiological parameters in thromboembolic complications in patients with acute calculous cholecystitis (ACC).